2021
DOI: 10.4062/biomolther.2020.064
|View full text |Cite
|
Sign up to set email alerts
|

Antaroide, a Novel Natural Nine-Membered Macrolide, Inhibits Melanin Biosynthesis in B16F10 Murine Melanoma Cells

Abstract: The demand for natural substances with anti-melanogenic activity is increasing due to the recent interest in skin whitening. Intensive investigation on the culture broth of Streptomyces sp. SCO-736, a marine bacterium from the Antarctica coast, has led to the isolation of a new natural product named antaroide (1). The chemical structure was established through the interpretation of MS, UV, and NMR spectroscopic data. Antaroide is a nine-membered macrolide with lactone and lactam moieties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…e etiology of pigmentation is not well understood. Melanin biosynthesis is catalyzed by melanocyte-specific enzymes such as TRP-1 and TRP-2 [34]. Tyrosinase is vital to melanocyte melanin biosynthesis and has been known for many decades [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e etiology of pigmentation is not well understood. Melanin biosynthesis is catalyzed by melanocyte-specific enzymes such as TRP-1 and TRP-2 [34]. Tyrosinase is vital to melanocyte melanin biosynthesis and has been known for many decades [34].…”
Section: Discussionmentioning
confidence: 99%
“…Melanin biosynthesis is catalyzed by melanocyte-specific enzymes such as TRP-1 and TRP-2 [34]. Tyrosinase is vital to melanocyte melanin biosynthesis and has been known for many decades [34]. erefore, tyrosinase is an important index for the treatment of pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…45 Two antibiotic dixiamycins 138 and 139 from Streptomyces olivaceus displayed activities against seven bacterial strains ranging from potent to no antibacterial activity. 46 Other Streptomyces strains yielded antaroide 140, a new nine-membered macrolide that was shown to inhibit melanin biosynthesis in murine melanoma cells, 47 Genome sequencing of this strain revealed the presence of a BGC that encoded for glycosylated type I PKS and additional studies showed that the BGC associated with venturicidin biosynthesis (ven) was supported by the proposed biosynthetic pathway and conrmed by inactivation of the core PKS gene venK. 68 As with previous reviews in this series, a number of new bacterial MNPs were claimed during 2021, but the structures presented were not fully consistent with the spectroscopic evidence provided.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
“…45 Two antibiotic dixiamycins 138 and 139 from Streptomyces olivaceus displayed activities against seven bacterial strains ranging from potent to no antibacterial activity. 46 Other Streptomyces strains yielded antaroide 140 , a new nine-membered macrolide that was shown to inhibit melanin biosynthesis in murine melanoma cells, 47 two antibacterial pyrrolobenzodiazepine derivatives 141 and 142 , 48 a new polycyclic tetramate macrolactam, koyanamide A 143 , 49 a new butenolide derivative 144 , featuring an octyl substitution at the γ-position, 50 two angucyclinone derivatives, gephyyamycin 145 and cysrabelomycin 146 , 51 and TMKS8A 147 , a new antibacterial chlorinated α-lapachone derivative, that was identified from the culture extract of a Streptomyces strain that was obtained from a sea slug. 52 Marinoterpins A–C 148 , 149 and 150 were isolated from the culture broth extracts of two actinomycetes associated with the family Streptomycetaceae and represent new chemical motifs as they combine quinoline- N -oxides with linear sesterterpenoid side chains.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…The etiology of pigmentation remains relatively enigmatic. The cascade of melanin biosynthesis hinges on melanocyte-specific enzymes such as TRP-1 and TRP-2 (Ryu et al 2021). Hence, tyrosinase emerges as a pivotal gauge in addressing pigmentation concerns.…”
Section: Genetic Investigationmentioning
confidence: 99%